Escolarização, trabalho e cidadania : a educação de adultos no Brasil no século XIX - Nogueira, Vera Lúcia; Faria Filho, Luciano Mendes de (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
This article presents a study of public and private initiatives of adults education and instruction, developed through night classes, in varied spaces the sociability network of Brazilian provinces, which dates from the second half of the nineteenth century. Taking as sources, newspapers of the Annals of the Legislative Assembly Provincial, province residents messages, schools inspection reports, all of which are available in Brazilian Digital Periodicals of Minas Gerais Public File. We attempted to incorporate the repertoires used by different subject which promised to marginalized Brazilian population, varied cultural spaces of sociability network in which developed the initiatives and education, instruction. It was found that Brazilian citizens have built a framework of strategies of socialization to transform the traditions, behaviors and the mentality of the poor adult population, free, naive or slaved, with purpose to civilize them, as well as inserting them the broader project of building a modern nation